Pemikiran Fazlur Rahman (Pragmatis-Instrumental) tentang Pendidikan dan Relevansinya dengan Dunia Modern - Luthfi Hibatullah; Ahmad Qomarudin (AS-SABIQUN, 2021)
In the world of education the dichotomy between religion and general science is no longer a new problem in the Islamic education system. This discourse has emerged for a long time and is still a complex issue that has not been resolved. This is due to the boundary between religious and non-religious studies taught in each educational unit. From this, Fazlur Rahman proposed the idea of ​​reforming all Islamic education systems. What is gained from experience, making observations and various research. So this research focuses on the intellectual biography of Fazlur Rahman, Fazlur Rahman’s educational thoughts and educational thoughts in Indonesia, and the relevance of the two. In this study the authors used data collection methods with documentation methods, which are in data collection techniques in library research (library research).